Pengaruh Pengembangan Karir dan Kepuasan Kerja Perawat Terhadap Komitmen Organisasi RS. Eka Hospital Pekanbaru - Susi Susanti; Susi Hendriani; Chairul Amsal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study was conducted at Hospital Eka Hospital Pekanbaru. The purpose of this study was to determine the effect of partial and simultaneous career development and job satisfaction. The number of samples in this study were 73 hospital nurses Eka Hospital Pekanbaru. From the results of the ttest with two-way career development is known that variable with a value of tcount> ttable or 6,475 > 2,00 so the career development of partial positive effect on organizational commitment. Furthermore, job satisfaction variable with a value of t > t table or 4,576 > 2,00 and thus job satisfaction partially positive effect on organizational commitment. F test results with values of Fcount = 41,624 and Ftable = 3,13 so F value is greater than the F table and a significance value of F is 0,000 less than the α value of 0,05. Thus, simultaneous career development and job satisfaction affects organizational commitment RS Eka Hospital Pekanbaru. Advice can be given to the hospital is expected Eka Hospital Pekanbaru in order to instill cultural values of the organization, provide information clearly and evaluate career and rearranging the placement of the system to match the position of nurses and nurse expertise. Furthermore, nurses are expected to strive for in order to prioritize the organization's willingness to put the interests of the affairs of the hospital in advance rather than private interests, more daring in the face of challenging work and mutual support among nurses.Keywords: Career Development, Job Satisfaction, OrganizationalCommitment